Seismic soil-structure interaction in performance-based design - Lu, Yang (2016)
Soil-Structure Interaction (SSI) procedures for performance-based seismic design of building structures have been in existence in design guidelines and provisions for decades. However, several issues still remain regarding the application of these procedures to inelastic multi-storey buildings. Three main issues are identified and investigated in this research.